2021
DOI: 10.1016/j.cmpb.2020.105920
|View full text |Cite
|
Sign up to set email alerts
|

Pathological myopia classification with simultaneous lesion segmentation using deep learning

Abstract: Purpose: To assess the use of deep learning for detection of pathological myopia (PM) and semantic segmentation of myopia-related lesions from fundus images. Methods: This investigation reports on the results of deep learning models developed for the recently introduced Pathological Myopia (PALM) dataset, which consists of 1200 images. Evaluation metrics include area under the receiver operating characteristic curve (AUC) for PM detection, Euclidean distance for fovea localization, and Dice and F1 metrics for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…In recent years, with the rapid development of the artificial intelligence technology and deep learning methods, many researchers have applied them to various image processing problems. New techniques and methods that analyze fundus images for high myopia have been continuously emerging [ 5 , 6 , 7 , 8 , 9 , 10 ]. These methods use computer-aided technologies to automatically analyze and diagnose lesions associated with high myopia in the absence of experienced ophthalmologists and professional optometry instruments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, with the rapid development of the artificial intelligence technology and deep learning methods, many researchers have applied them to various image processing problems. New techniques and methods that analyze fundus images for high myopia have been continuously emerging [ 5 , 6 , 7 , 8 , 9 , 10 ]. These methods use computer-aided technologies to automatically analyze and diagnose lesions associated with high myopia in the absence of experienced ophthalmologists and professional optometry instruments.…”
Section: Introductionmentioning
confidence: 99%
“…The first task of the 2019 PALM Color Fundus Photographic Pathological Myopia Challenge [ 8 ] was the qualitative classification of pathological myopia. Participating teams used different CNN models [ 9 , 10 , 11 ] to predict the risk of pathological myopia using fundus images. However, these classifications only distinguished pathological myopia from nonpathological myopia, and certain fundus images classified as nonpathological myopia still have a certain high myopia risk (such as “simple high myopia” defined in [ 3 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Automatic diagnosis of retinal detachment and/or PMCNV by fundus photographs has been reported in some studies ( 25 , 26 ). Hemelings et al developed an algorithm for PM detection using 400 fundus photographs, and the F1 score for retinal detachment was 0.71 ( 25 ).…”
Section: Discussionmentioning
confidence: 97%
“…Some researchers have performed automatic identification and segmentation of myopic lesions based on fundus photographs, and achieved promising performance ( 25 28 ). Tan et al developed an algorithm which achieved high diagnostic performance, with an AUC of 0.913 for high myopia and 0.969 for myopic maculopathy ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing demographic and clinical information, retinal fundus photograph data and genotyping data from 2,258 subjects, this method achieved an AUC of 0.888 and outperformed the detection results obtained from the use of demographic and clinical information (an AUC of 0.607), imaging data (an AUC of 0.852) or genotyping data (an AUC of 0.774) alone, with increases of 46.3%, p < 0.005; 4.2%, p = 0.19; and 14.7%, P < 0.005, respectively. Recently, Hemelings et al ( 39 ) developed a successful approach based on a DL algorithm for the simultaneous detection of PM, with an AUC of 0.9867, and the segmentation of myopia-induced lesions. Other similar studies have also been reported, such as those identifying the different types of lesions of myopic maculopathy automatically from fundus photographs with DL models ( 40 , 41 ).…”
Section: Ai In the Detection And Diagnosis Of Myopiamentioning
confidence: 99%